Catálogo colectivo de fondo antiguo en materia de actividad física y deporte. - Hernández Pérez, Antonio (Revista General de Información y Documentación, 2000)
Ihe text presents the results of a research on te ancient books holdings In Spanish language concerning physical activity and sport. Ihe producí resul ting from this research includes a database running on Micro Isis fWinisis, with almost 2000 references, plus a document depository in hypertext format (HTML) including the records of the 2000 documents, over 200 photographs, hundreds of authors and publishers' biographies and more tan 6000 links among the various generated indexes. This document depository may be acces sed through the Internet or by CD-ROM, requiring just a web pages viewer.
Keywords: Ancient books; sport; Spain; Union catalog; Latin America